Surface Modification Of Polyethersulfone Membrane Via Uv-Grafting for Forward Osmosis Technology - Ahmad Fikri Hadi, Abdul Rahman; Mazrul Nizam, Abu Seman (The Malaysian Analytical Sciences Society, 2018)
In this study, UV-grafting was used in surface modification of polyethersulfone membrane (UFPES50) for forward osmosis (FO) application. Using two parameters, namely monomer concentration (acrylic acid) and grafting time, the modified membrane was characterised by attenuated total reflectance-Fourier transform infrared (ATR-FTIR), field emission scanning electron microscope (FESEM) and contact angle. The membrane was evaluated for its water permeability, solute permeability, and structural parameter. The water permeability increases as the grafting parameters increases; however, at the highest (50 g/L) monomer concentration, a sudden drop occurred due to the thickening of the grafted layer. Focusing on this monomer concentration, the grafting time was increased up to 60 minutes and it was successfully demonstrated that the modification using UV-grafting on PES membrane involved both effective grafting and chain scission. In addition, negative rejection on the modified membrane was observed